Diversity and species composition of lichens across altitudinal range in the Batang Toru Forest, North Sumatra, Indonesia - NURSAHARA PASARIBU; OKY KUSUMA ATNI; JULIUS PAOLO SIREGAR (Society for Indonesian Biodiversity, 2023)
Abstract. Pasaribu N, Atni OK, Siregar JP. 2023. Diversity and species composition of lichens across altitudinal range in the Batang Toru Forest, North Sumatra, Indonesia. Biodiversitas 24: 2171-2178. West Block of Batang Toru Forest, located in North Tapanuli Regency, North Sumatra is one of the protection forest areas which has uniqueness and high biodiversity, one of them is the lichen. The information regarding the lichen species found in the West Block of Batang Toru Forest Research Station has never been reported. Its various types and distributions are unknown. This study aimed to observe lichen at the Batang Toru Forest Research Area, which was carried out from September 2021 to March 2022. The study was carried out with the exploration method by exploring along the track. From the results of the study, there was a total of 54 species of lichen consisting of 23 families and 38 genera. Based on the types of the thallus, it was found 23 species of lichen classified as foliose, 21 crustose, 4 fruticose, 3 squamulose, and 3 filamentous. The most common lichen family found at the study site was Lobariaceae, with a total of six species. The species collected in this study were mostly found on the bark substrate. This study reveals important information about the variety of lichen species in the West Block of Batang Toru Forest, highlighting the urgent need for further research and conservation efforts to protect this unique and diverse ecosystem.